The Mediating Role of Attitude Toward Product Towards Halal Cosmetic Purchase Intention in Female Consumers in Indonesia - Boginskaya Letsoin; Sri Vandayuli Riorini (Journal of Social Research, 2023)
The halal industry has now become a world rend and has increased consumer opportunities every year. The State Global Islamic Economic Report 2020-2021 shows that world consumption in the halal industry reached USD 2.02 trillion The purpose of this research is to identify factors that can increase the purchase intention of local Indonesian halal cosmetic brands with attitude mediation. The sample of this study were female consumers who had bought serum, lip cream and lipstick from local halal cosmetic brands (Wardah, Emina and Make Over). In this study, the amount of data processed was 258 respondents who were analyzed using the SEM statistical analysis method with the help of LISREL 8.0. The results of the study show that brand image, perceived value, religious belief, halal certification have a positive and significant role in attitude. Brand image, perceived value, religious belief, halal certification and attitude have a positive and significant role on purchase intention. Subjective norms do not have a significant role on attitude or purchase intention. The results of the mediation role test found that attitude has a role as a mediator between brand image, perceived value, religious belief and halal certification on purchase intention. The conclusion of this study is that subjective norms are not one of the factors that can increase halal cosmetic purchase intention and attitude has a role as a partial mediator on purchase intention. The implication of this research is that managers must improve brand image, perceived value, religious belief, halal certification, subjective norms, attitude and purchase intention to attract consumers to buy local halal cosmetic brands. In future research, it is necessary to expand the respondent's domicile to better describe Indonesian female consumers in general.